Hotel rooftops as a space for consumption in historic centres: the case study of Palma (Spain). - Mercade-Mele, Pere; Almeida-García, Fernando; Martínez-García, Aitor; Coll-Ramis, Miquel Ángel (MDPI, 2023)
This research analysed the transformation of hotel rooftops in the historic centre of Palma into new spaces for tourist consumption. Nowadays, tourists are looking for unique and special experiences, which has led tourist destinations to seek new attractions to offer. Rooftops are becoming privileged places and provide a differential experience, leading to an increase in the offer of tourist services on hotel rooftops. This study explored the change of use in hotel rooftops in historic city centres for the commercialization of tourism. In this sense, this research sheds light on the factors that influence the commodification of rooftops and the attributes that are most valued by users in Google Maps and TripAdvisor reviews of their experiences. Furthermore, the transformation of rooftops has not followed a single model of commodification, but different typologies were identified according to uses and access modalities. Finally, implications for the city’s tourism planning and management are presented.
Keywords: Palma de Mallorca; Turismo social; Azoteas; Consumo (Economía); Turismo - Aspectos económicos - Palma (Mallorca, Islas Baleares); Landscape consumption; Palma; Rooftops; Tourism commodification; Tourist experiences